A quantum wavepacket study of three-dimensional Ne-H2+ scattering - Gogtas, F; Oturak, H; Bulut, N; Akpinar, S; Kökce, A (Taylor & Francis Ltd, 2003)
The state-to-state and state-to-all reaction probabilities have been calculated for three-dimensional reactive and inelastic scattering of Ne + H-2(+)(v = 0, j = 0, 1, 2) at zero total angular momentum. The time-dependent Schrodinger equation is solved by means of Fourier grid and discrete variable representation techniques. The inelastic and reactive scattering probabilities for a broad range of energies are calculated. Although the system has an open reactive channel, the results show that a high fraction of the flux is reflected back due to endoergicity and potential barriers leading to inelastic scattering.
Keywords: Wave-Packet Approach; Reactive Scattering; Molecular Photofragmentation; Schrodinger-Equation; Cross-Sections; Dynamics; Distributions; Surface